2019
DOI: 10.3390/sym11060822
|View full text |Cite
|
Sign up to set email alerts
|

The Computer Course Correlation between Learning Satisfaction and Learning Effectiveness of Vocational College in Taiwan

Abstract: In this paper, we surveyed the influence of learn effectiveness in a computer course under the factors of learning attitude and learning problems for students in senior-high school. We followed the formula for a regression line as R = A + BX +ε and simulated on SPSS platform with symmetry to obtained the results as follows: (1) In learning attitude, both the cognitive-level and behavior-level, are positively correlated with satisfaction. This means the students have cognitive-level and behavior-level more posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Chen and Tu [ 5 ] investigated the effect of learning attitudes and problems on learning outcomes among high school students in computer courses. They determined that learning attitudes were positively correlated to satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Chen and Tu [ 5 ] investigated the effect of learning attitudes and problems on learning outcomes among high school students in computer courses. They determined that learning attitudes were positively correlated to satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al reported "The Computer Course Correlation between Learning Satisfaction and Learning Effectiveness of Vocational College in Taiwan" [20]. In this paper, the authors surveyed the influence of learning effectiveness in a computer course under the factors of learning attitude and learning problems for students in senior-high school.…”
Section: Lan Et Al Reported "Symmetric Modeling Of Communication Effectiveness and Satisfactionmentioning
confidence: 99%